Cases in management and organizational behavior - Tompkins, Teri C. (Prentice Hall, 2001)
Realistic, intermediate-length cases make up this inexpensive casebook. Based on real events but with all names changed, the cases either illustrate theory or describe a recent real-life dilemma requiring a decision. Cases are long enough to require significant analysis from the reader, but short enough that a wide variety of topics can be covered. Describes the full range of management, systems, group, interpersonal, and individual topics; also highlights international business, globalization, diversity, ethics, communications, and human resource decisions. References each case to several leading management and organizational behavior books. Offers a versatile range of material and organization, making book suitable for a variety of uses. An inexpensive, handy reference for trainers, organizational development consultants, and other Human Resources professionals.